Signatures of selection in the Iberian honey bee (Apis mellifera iberiensis) revealed by a genome scan analysis of single nucleotide polymorphisms. Issue 23 (7th November 2013) - Chávez‐Galarza, Julio; Henriques, Dora; Johnston, J. Spencer; Azevedo, João C.; Patton, John C.; Muñoz, Irene; De la Rúa, Pilar; Pinto, M. Alice
Abstract Understanding the genetic mechanisms of adaptive population divergence is one of the most fundamental endeavours in evolutionary biology and is becoming increasingly important as it will allow predictions about how organisms will respond to global environmental crisis. This is particularly important for the honey bee, a species of unquestionable ecological and economical importance that has been exposed to increasing human‐mediated selection pressures. Here, we conducted a single nucleotide polymorphism (SNP)‐based genome scan in honey bees collected across an environmental gradient in Iberia and used four FST‐based outlier tests to identify genomic regions exhibiting signatures of selection. Additionally, we analysed associations between genetic and environmental data for the identification of factors that might be correlated or act as selective pressures. With these approaches, 4.4% (17 of 383) of outlier loci were cross‐validated by four FST‐based methods, and 8.9% (34 of 383) were cross‐validated by at least three methods. Of the 34 outliers, 15 were found to be strongly associated with one or more environmental variables. Further support for selection, provided by functional genomic information, was particularly compelling for SNP outliers mapped to different genes putatively involved in the same function such as vision, xenobiotic detoxification and innate immune response. This study enabled a more rigorous consideration of selection as the underlying cause of diversity patterns in Iberian honey bees, representing an important first step towards the identification of polymorphisms implicated in local adaptation and possibly in response to recent human‐mediated environmental changes.